2020
DOI: 10.1021/acsomega.9b04076
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Ag-TiO2 Nanofibers for Photocatalytic Glucose Conversion to High-Value Chemicals

Abstract: TiO 2 nanofibers were fabricated by combination of sol−gel and electrospinning techniques. Ag-doped TiO 2 nanofibers with different Ag contents were prepared by two different methods (in situ electrospinning or wetness impregnation of Ag on TiO 2 nanofibers) and heat treated at 500 °C for 2 h under an air or N 2 atmosphere. The obtained catalysts were characterized by field emission scanning electron microscopy, X-ray diffraction, photoluminescence, and N 2 adsorption analyzed by the Brunauer− Emmett−Teller (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…In comparison, the product distribution was similar to the previous reports based on the oxidation pathway. 15 , 44 However, the difference on selectivity of the derived products was observed in the presence of the Cr–TiO 2 -supported photocatalyst. 14 In addition, the use of rutile TiO 2 -based photocatalysts also resulted in different selective oxidation patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the product distribution was similar to the previous reports based on the oxidation pathway. 15 , 44 However, the difference on selectivity of the derived products was observed in the presence of the Cr–TiO 2 -supported photocatalyst. 14 In addition, the use of rutile TiO 2 -based photocatalysts also resulted in different selective oxidation patterns.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have been reported for conversion of sugars to several chemicals, for example, gluconic acid, formic acid, arabinose, and arabitol. 10 , 14 , 15 In addition, xylitol was also found from photocatalytic glucose conversion. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 displays the XRD spectra of various samples. The XRD spectra of TiO 2 NFs showed several peaks at 2θ values of 27.35°, 36.0°, 41.2°, 54.25°, 56.55°, 62.75°, 63.9°, and 68.95°, which correspond to (1 1 0), (1 0 1), (1 1 1), (2 1 1), (2 2 0), (0 0 2), (3 1 0), and (3 0 1) crystal plane of rutile, respectively [ 31 , 42 ]. Similarly, the peaks at 25°, 38°, and 47.89° matched with the crystal planes of (1 0 1), (0 0 4), and (2 0 0) anatase TiO 2 , respectively [ 31 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous precedents reporting on dye pollutant decomposition with TiO 2 nanocomposites, the utilization of Ag NPs-embedded TiO 2 nanofibers is scarce for this purpose [ 33 , 34 , 35 ]. Hence, these nanofibers were assessed in this study for their ability to harness solar energy and degrade two representative organic dyes, namely RhB and MO, providing us with valuable insights on the photocatalyst’s performance on xanthene and azo classes of dye, respectively.…”
Section: Introductionmentioning
confidence: 99%